Opportunities in ODL Mode of Education: University-Level Students' Perspectives - Joshi, Bishnu Maya; Acharya, Umesh; Khatiwada, Shambhu Prasad (Butwal Campus Journal, 2024)
This study investigates how ODL has significantly shaped the educational paradigm and enriched students' learning experiences concentrating specifically on students affiliated with Tribhuvan University. This study adopted a quantitative research approach, leveraging a cross-sectional survey design to capture comprehensive student motivation insights. The data collection involved structured Google Forms questionnaires, ensuring efficiency and reliability in gathering diverse perspectives. The research employed a census method to encompass a representative sample of respondents, enhancing the generalizability of findings. The total number of respondents was 145, taken from all students enrolled in the ODL mode of education, Mahendra Ratna campus, Tahachal, and Central Department of Education, Kirtipur. Descriptive statistics, encompassing mean and standard deviation, were computed for each Likert scale item, offering to examine the respondents' responses. One sample t-test and one-way ANOVA, were used to show the status of opportunities offered by respondents and significant differences between various demographic variables. The study's survey results reveal positive perceptions among students regarding the opportunities presented by ODL, emphasizing convenience, flexibility, and improved IT skills. The study also explores the statistically significant differences observed in perceived opportunities based on gender. The study underscores the positive impact of ODL on students' educational experiences and highlights its potential to reshape the future of learning in an interconnected world.